1999
DOI: 10.1046/j.1365-8711.1999.02771.x
|View full text |Cite
|
Sign up to set email alerts
|

Multisite observations of surface structures on AB Doradus in 1994 November

Abstract: We present time‐resolved optical spectroscopy and broad‐band photometry of the rapidly rotating southern K0 dwarf star AB Doradus, obtained during 1994 November. The data were obtained as part of a collaboration dedicated to MUlti‐SIte COntinuous Spectroscopy (MUSICOS), and entailed coordinated observations on three continents to obtain the fullest phase coverage possible subject to limitations of local weather conditions. The Doppler images from the three consecutive nights of the run show excellent mutual ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…AB Dor, however, remains the most studied object to date. Prominences have consistently been reported (Collier Cameron & Robinson 1989a,b; Donati & Collier Cameron 1997; Collier Cameron et al 1999; Donati et al 1999) to lie at a range of distances from the stellar rotation axis from 2 to 8 R * , with a concentration at the corotation radius (2.7 R * on AB Dor).…”
Section: Introductionmentioning
confidence: 81%
“…AB Dor, however, remains the most studied object to date. Prominences have consistently been reported (Collier Cameron & Robinson 1989a,b; Donati & Collier Cameron 1997; Collier Cameron et al 1999; Donati et al 1999) to lie at a range of distances from the stellar rotation axis from 2 to 8 R * , with a concentration at the corotation radius (2.7 R * on AB Dor).…”
Section: Introductionmentioning
confidence: 81%
“…The AB Dor prominence system remains the most studied to date. Prominences have consistently been reported (Collier Cameron & Robinson 1989a,b; Donati & Collier Cameron 1997; Collier Cameron, Walter & Vilhu 1999; Donati et al 1999) to lie at a range of distances from the stellar rotation axis from 2 to 8 R * , with a concentration at the co‐rotation radius (2.7 R * on AB Dor).…”
Section: Introductionmentioning
confidence: 84%
“…Strassmeier 1999;Collier-Cameron et al 1999;Berdyugina et al 1998;Barnes et al 1998), differential rotation both in the same sense and in the opposite sense than on the Sun (Vogt et al 1999;Donati & Collier-Cameron 1997;Hatzes 1998;Rice & Strassmeier 1996;Barnes et al 2001), possibly detected meridional flows toward the pole (Weber & Strassmeier 2001;Strassmeier & Bartus 2000), detected and mapped prominences (Collier-Cameron et al 1999) and warm spots (Piskunov 1996;Unruh et al 1998;Strassmeier 1999), observed active longitudes and related activity flip-flops (Berdyugina et al 1999), found spot evolution on very short-and on very long timescales (e.g. Washuettl et al 2000;Barnes et al 1998) and, finally, directly detected complex magnetic surface fields (Wade et al 2000;Piskunov & Kochukhov 2001).…”
Section: Surface Imaging Of Solar-type Stars and What Does It Tell Usmentioning
confidence: 99%